Factors Determining the Success of Pradhan Mantri MUDRA Yojana : A Study of North India - Singh, Khujan; Kumar, Anil (Indian Journal of Finance, 2020)
The present study was a primary data-based research work in which attempt was made to identify the determinants of Pradhan Mantri MUDRA Yojana. For this study, data were collected with the help of a designed questionnaire and the respondents for the study were branch managers, assistant managers, and other responsible employees of public and private sector commercial banks. A total of 161 questionnaires were filled, although we approached more than 480 respondents at their branch locations. The reliability and validity of the collected data were tested by employing Cronbach’s alpha. Furthermore, the data were analyzed by employing exploratory factor analysis with the help of SPSS. The study found six determinants of success of PMMY, and these determinants are responsible for creating awareness in weaker sections about start-ups and job creator non-funded individuals. This scheme is suitable for both banks and borrowers because this scheme does not require any collateral. Therefore, it should be continued by the Central government as it is a very close substitute of the other loan schemes. The results of this study will be quite useful for the Government of India, commercial banks, and other financial institutions in the marketing of this scheme in disbursement of loans to the rural & urban unemployed and non-funded individuals.